A system for accounting the costs of contemporary negative environmental phenomena - some methodological remarks: none - Czaja, Stanisław; Becla, Agnieszka (Economics and Environment, 2022)
The article contains an idea of building a cost accounting system for contemporary negative phenomena of natural and anthropogenic disasters, including ecological ones. These phenomena are treated as "black swans", that is, phenomena with a high level of threat and wide, diverse, mainly negative effects. The authors presented selected methodological suggestions for including different types of effects of such phenomena in the system of records and their monetary valorization (i.e. cost recognition). The article is intended as an introduction to further in-depth discussion of these challenges. Considering the emerging problems (phenomena and processes), they belong to the most important issues for economics, ecological economics and environmental economics. However, they are not very often addressed in the literature.